The Effectiveness of a Vlog-Integrated Project-Based Learning Model on Culinary Arts Learning Achievement - Asnur, Lise; Weriza, Jusmita; Fajri Putri, Meddiati (International Journal of Environment, Engineering and Education, 2025)
Project-Based Learning (PjBL) is a constructivist learning model that emphasizes active student engagement through real-world projects. Implementation in vocational education often faces challenges such as limited time, high material costs, and procedural errors. This study aims to evaluate the effectiveness of integrating vlogs into Project-Based Learning, or Project-Based Learning with Vlog (PjBLV), in improving learning readiness, reducing procedural errors, and enhancing students’ culinary practicum outcomes. Employing a quasi-experimental design with a nonequivalent control group, the research involved 26 third-semester students of the Hospitality Management Program at Universitas Negeri Padang, divided equally into an experimental group (PjBLV) and a control group (PjBL). The instruments consisted of a pre-test, essay-based post-test, and practicum assessment, all validated and tested for reliability. At the same time, data were analyzed using N-Gain and independent t-tests at a 0.05 significance level. Findings revealed that the experimental group achieved a higher post-test mean score (88.67) than the control group (84.42), with an N-Gain of 80.46% categorized as high, indicating significant improvement in learning outcomes. The consistent distribution of scores demonstrated that PjBLV benefitted students across different ability levels, thereby reducing performance gaps. PjBLV proved more effective than conventional PjBL by promoting time efficiency, minimizing errors, and optimizing resources. The implications suggest that PjBLV is a promising pedagogical model for broader application in vocational education. Future studies are recommended to examine its impact on long-term skill retention and to explore the integration of interactive, technology-enhanced vlog-based learning for more personalized instruction.